Relative Efficacy of Sewage as Compared to Ammonium Sulphate and Superphosphate on Equivalent Basis in Berseem Crop - Srivastava, S.P. (Journal of Soil and Water Conservation, 2022)
The disposal of sewage is becoming a problem with rapid industrialisation of the country. The safest and effective utilisation of human waste lies in crop production. Although human waste offers great promise in agriculture but its ill planned use is associated with grave consequences. Therefore, selection of soil, crop and proper method of application are of immense importance. In past (Das 1948, Parr and Bose 1944), activated sludge was compared with fertilizers and not the sewage effluent, which offers greater promise for use. In some cases, sewage effluent was just compared with canal water also (Talati 1942 and Day and Tucker 1955). However, Singh (1965) has advocated dilution of sewage effluent by 1/3 with water for obtaining best yields in wheat crop. It will be more useful if first two irrigations are of sewage and third is of pure water than mixing them every time. Consequently in this experiment on berseem, out of ten irrigations, only six were sewage irrigation and rest four were ordinary water. Subsequently the sewage effluent was compared on equivalent basis with fertilizers.